Modern formats of graphic novels as a tool of continuity of ethnocultural traditions in the upbringing and education of youth and adolescents - Sebenova, Bagda; Mikhailova, Natalia (Pedagogy and Psychology, 2021)
This article describes such modern formats of literary and graphic genres as manga and comics (including ranobe, manhwa, and manhua). Graphic novels are currently relevant all over the world, especially among young people. Graphic novels of this type are actively promoted in the mass media and pop culture. These picture books received the attention and adaptation not only of small film studios and book publishers, but also of the cinematic giant – Hollywood. Due to the interest of the younger generation in the format of comics, this genre can be used to promote ethnocultural traditions in the education and education of the younger generation with an orientation on the national characteristics of the country and the values ​ ​ of Kazakh art and culture. Such an axiological dialogue of the culture of near and far ethnic systems will certainly contribute to the development of interest in national heritage, since the conversation will be conducted in an accessible language of images and in the original presentation using modern graphic formats and genres.